Irenaeus : Life, Scripture, Legacy - Foster, Paul, 1966-; Parvis, Sara (Book collections on Project MUSE., 2012)
"Champion of martyrs, scourge of heretics, erudite theologian, shrewd politician, no account of early Christianity is complete without careful consideration of Irenaeus of Lyons. Here a team of international scholars examines aspects of the saint's life, historical context, engagement with scripture, and his ecclesiastical and theological legacy for succeeding generations."--Publisher description